2014
DOI: 10.1007/s10816-014-9225-8
|View full text |Cite
|
Sign up to set email alerts
|

Andean Ores, Bronze Artifacts, and Lead Isotopes: Constraints on Metal Sources in Their Geological Context

Abstract: With a focus on bronze production in the south-central Andes during the Middle Horizon, this study reports the first archaeological use of lead isotope analysis to investigate metallic ores and metal artifacts in the Andean zone of South America. Because the vast majority of metal deposits in the Andean cordillera formed in a convergent plate boundary setting, lead isotope compositions of most Andean ore sources are not unique. Lead isotope ratios of central and south-central Andean ores define four geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 72 publications
4
48
0
5
Order By: Relevance
“…El estudio también evaluó el origen geoquímico de 16 hachas a través de isótopos de plomo, determinándose que habrían sido elaboradas a partir de menas altiplánicas, descartando a SPA como proveedor de las materias primas o productor de tales artefactos, aunque podrían haber sido manufacturadas en la aleación Cu-As-Ni proporcionada por Tiwanaku. Tres hachas podrían provenir desde menas cupríferas próximas a los oasis de SPA (Macfarlane y Lechtman 2015), las cuales desgraciadamente no sabemos si corresponden o no a los objetos elaborados en cobre no aleado.…”
Section: ¿Altiplánicos O Atacameños?unclassified
See 2 more Smart Citations
“…El estudio también evaluó el origen geoquímico de 16 hachas a través de isótopos de plomo, determinándose que habrían sido elaboradas a partir de menas altiplánicas, descartando a SPA como proveedor de las materias primas o productor de tales artefactos, aunque podrían haber sido manufacturadas en la aleación Cu-As-Ni proporcionada por Tiwanaku. Tres hachas podrían provenir desde menas cupríferas próximas a los oasis de SPA (Macfarlane y Lechtman 2015), las cuales desgraciadamente no sabemos si corresponden o no a los objetos elaborados en cobre no aleado.…”
Section: ¿Altiplánicos O Atacameños?unclassified
“…La aleación Cu-As-Ni corresponde a la firma altiplánica por excelencia, particularmente porque se encuentra espacial y temporalmente circunscrita a la región altiplánica durante el PM (Macfarlane y Lechtman 2015). Se hace presente desde el siglo II en el área de influencia Tiwanaku, siendo característica de los metales más tempranos distribuidos por esta órbita.…”
Section: Altiplano Bolivianounclassified
See 1 more Smart Citation
“…Once these ores are smelted and cast into metal objects, variations in the resulting lead isotope ratios provide an opportunity for differentiating one metal supply from another. One comparative example is that provided by Macfarlane and Lechtman () in regard to the provenance of prehistoric Andean bronze metallurgy. Variations in local geological contexts allowed them to delineate several strongly discriminated lead isotope provinces in a west–east direction from the coastlines of Peru and Chile to the Andean Mountains.…”
Section: Introductionmentioning
confidence: 99%
“…The area is composed of coastal and volcanic arc sediment deposited on to a basement of Mesozoic and Paleozoic sedimentary and metamorphic rock . Province I lead has been found ) which corresponds to the known isotopic composition of orogenic lead (Zartman andDoe 1981 andLechtman 2014). and Gunnesch et al (1990) teams determined that the isotopic signatures found in the rocks of Province I derived from mixing of crustal rock melt and the magmatic source.…”
Section: Province Imentioning
confidence: 77%